Long-term ultra-marathon running and arterial compliance - Burr, J. F.; Drury, C. T.; Phillips, A. A.; Iveya, A.; Kua, J.; Warburton, D. E. R. (Journal of Science and Medicine in Sport, 2014)
Recent reports that habitual marathon runners demonstrate higher levels of stiffness and cardiovascular risk factors have been of great interest to the medical and scientific community. Ultra-marathon running, that is any distance >42.2 km, is increasing in popularity; however, little is known regarding the physiological effects of the sport's unique training and racing practices on vascular health. Objectives: To characterize and compare the arterial compliance of male long-term (>5 years) ultra-marathoners with recreationally active controls, and examine the associations of training related practices with systemic arterial compliance. Design: We employed a case-control comparison design using long-term habitual ultra-marathon runners (n = 18) and an age matched cohort of normative recreationally active males. Methods: Arterial compliance was measured at rest using radial applanation tonometry (CR-2000, HDI) for diastolic pulse contour analysis. Compliance was compared with normative data, participant characteristics, and associated exercise parameters. Results: In representative ultra-endurance runners, large artery compliance of long-term participants was reduced compared with physically active age-matched controls (p = 0.03) and is related to select training variables. Specifically, in a representative subset for whom we obtained detailed training data, decreased compliance was related to longer typical running distance per training session (r = -0.72, p = 0.03); however, more broad definitions of frequency, intensity, and duration revealed no association for the runners as a whole. Conclusions: Given the known associations of arterial stiffness with future cardiovascular events, ultra-endurance runners may be at an increased risk of a cardiovascular event compared with their normally active counterparts.